2013
DOI: 10.1152/ajpregu.00069.2012
|View full text |Cite
|
Sign up to set email alerts
|

Control of soluble fms-like tyrosine-1 (sFlt-1) production response to placental ischemia/hypoxia: role of tumor necrosis factor-α

Abstract: Although abnormal soluble fms-like tyrosine kinase-1 (sFlt-1) production is thought to be an important factor in the pathogenesis of preeclampsia (PE), the mechanisms that regulate the production of sFlt-1 during PE are unclear. While our laboratory has shown tumor necrosis factor-α (TNF-α) and sFlt-1 to be elevated in pregnant rats in response to placental ischemia, the importance of TNF-α in the regulation of sFlt-1 production is unknown. Therefore, the purpose of this study was to determine the role of TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 34 publications
(55 reference statements)
6
60
1
Order By: Relevance
“…We found that spiking the ELISA standard curves with ELP‐VEGF reduced the signal, suggesting that ELP‐VEGF might bind the Flt‐1 in the assay and prevent binding of 1 or both antibodies, thus confirming this as an assay for free sFlt‐1. Again, RUPP surgery resulted in a significant increase in free plasma sFlt‐1 (Figure 4C), consistent with previous reports 32, 36, 53, 56, 58, 63, 68. In contrast to the Western blot data, the ELISA data showed that ELP‐VEGF‐treated rats (both sham and RUPP surgical groups) had markedly reduced free sFlt‐1 levels (Figure 4C).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…We found that spiking the ELISA standard curves with ELP‐VEGF reduced the signal, suggesting that ELP‐VEGF might bind the Flt‐1 in the assay and prevent binding of 1 or both antibodies, thus confirming this as an assay for free sFlt‐1. Again, RUPP surgery resulted in a significant increase in free plasma sFlt‐1 (Figure 4C), consistent with previous reports 32, 36, 53, 56, 58, 63, 68. In contrast to the Western blot data, the ELISA data showed that ELP‐VEGF‐treated rats (both sham and RUPP surgical groups) had markedly reduced free sFlt‐1 levels (Figure 4C).…”
Section: Resultssupporting
confidence: 90%
“…These bands correspond to the report of Rajakumar,67 who describes sFlt‐1 bands of 145, 100, and 60 kDa in plasma from preeclamptic patients, though considerable species and glycosylation variation could exist. The RUPP surgery leads to a significant increase in plasma sFlt‐1, as has previously been reported 32, 36, 53, 56, 58, 68. This was confirmed in a separate cohort of rats, treated entirely independently with the sham or RUPP surgeries, and analyzed in a separate Western blot (Figure S1).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations